PENGUJIAN MINAT MAHASISWA AKUNTANSI UNIVERSITAS BAKRIE MENGGUNAKAN THEORY PLANNED OF BEHAVIOR (Media Riset Akuntansi, 2022)
This study aims to examine attitude toward the behaviour, subjective norms, perceived behavioural control and the level of education of the intention of accounting students at Universitas Bakrie for a career as a public accountant. The hypothesis is built using the Theory of Planned Behavior (TPB). The population in this research is the active S1 regular students of accounting studies at Universitas Bakrie in 2016-2019. Data collection techniques using a web-based questionnaire, through purposive sampling. Processing and data analysis in this study uses multiple linear regression. The results showed that the variables of attitude toward behaviour, subjective norms, and perceived behavioural control, positively influenced the intention of accounting students at Bakrie University for a career as a public accountant. In comparison, the study level variable does not affect the importance of considering students at Universitas Bakrie to pursue a career as a public accountant.